The Influence of Dosage and Frequency of Turi Leaf Liquid Organic Fertilizer (Sesbania grandiflora, L.) Application on the Growth and Yield of Land Spinach Plants (Ipomoea reptans Poir) - Aditya, Aprisa; Susilastuti, Darwati; Bachrun, Linda; Sunar; Husni, M.; Aditiameri; Suryanto, Toto (GoAcademica Research & Publishing, 2023)
This study aims to determine the effect of dosage and frequency of liquid organic fertilizer made from Turileaves on the growth and yield of land spinach plants (Ipomoea reptans Poir). The study used a factorial randomized block design (RBD) consisting of 2 factors. The first factor is the dosage of turi leaf liquid organic fertilizer consisting of 4 levels, namely, Turi Leaf LOF 0 ml/l (P0), Turi Leaf LOF 1.5 ml/l (P1), Turi Leaf LOF 3 ml/l (P2), Turi Leaf LOF 4.5 ml/l (P3). The second factor is the frequency of application consisting of 3 levels, namely application of LOF once a week (F1), application of LOF twice a week (F2), and application of LOF three times a week (F3). The results showed that the application of a dosage of 4.5 ml/l liquid organic fertilizer 3 times a week application gave the best results for plant height (30.60 cm), Number of Leaves (14 leaves), Stem Diameter (8.36 mm), Root Length (16.76 cm), and Harvest Weight (11.86 gr).